Impaired sensorimotor integration in parkinsonism and dyskinesia: a role for corollary discharges?. Issue 5 (May 1987) - Moore, A P
Abstract : In a bimanual slow matching task patients with asymmetric bradykinesia overestimated the movement of the more bradykinetic limb. Patients with drug induced or idiopathic asymmetric dyskinesia or dystonia, and patients with unilateral arm weakness underestimated movement of the abnormal limb. Bradykinesia may be caused by reduction, and dyskinesia and dystonia by exaggeration of corollary discharges.